Is a ‘Cast Iron Stomach’ Really That Strong? - Cooper-Dunn, Alice; Walker, Richard (Journal of Interdisciplinary Science Topics, 2017)
The term ‘cast iron stomach’ is reserved for people who never seem to succumb to the ill effects of bad food or drink. This paper assesses the credibility of having a cast iron stomach with respect to corrosion caused by gastric juices leading to potentially fatal symptoms. This point was taken to be when the cast iron stomach retained only 63% of its original mass whereby it is reasoned the stomach would rupture and likely lead to gastric juices leaking into the peritoneum. Through modelling the stomach to be a hollow sphere of stainless steel the time taken for corrosion to lead to gastric juices was found to be 34 days on average.